LH surge in Nelore cows (Bos indicus), after induced estrus or after ovarian superestimulation - Monteiro, Fabio Morato; Melo, Danilas Salinet; Ferreira, Marcelo Machado G.; Carvalho, Luciano Mundim; Sartoreli, Evandro Sartoreli e; Ederhardt, Bruno G.; Nogueira, Guilherme de Paula; Barros, Ciro Moraes (Elsevier, 2009)
Considering that there is limited information about the preovulatory LH surge in Zebu cattle (Bos indicus), the purpose of the present work was to assess the LH surge in Nelore cows during the estrous cycle and after ovarian superestimulation of ovarian follicular development with FSH. This information is particularly important to improve superovulatory protocols associated with fixed-time artificial insemination. Nelore cows (n = 12) had their estrus synchronized with an intravaginal device containing progesterone (CIDR-B ®) associated with estradiol benzoate administration (EB, 2.5 mg, i.m., Day 0). Eight days later all animals were treated with PGF2α (Day 8) in the morning (8:00 h) and at night, when CIDR devices were removed (20:00 h). Starting 38 h after the first PGF2α injection, blood sampling and ovarian ultrasonography took place every 4 h, during 37 consecutive hours. Frequent handling may have resulted in a stress-induced suppression of LH secretion resulting in only 3 of 12 cows having ovulations at 46.7 ± 4.9 and 72.3 ± 3.8 h, respectively, after removal of CIDR-B. Thirty days later, the same animals received the described hormonal treatment associated with FSH (Folltropin ®, total dose = 200 mg) administered twice a day, during 4 consecutive days, starting on Day 5. Thirty-six hours after the first injection of PGF2α, to minimize stress, only seven blood samples were collected at 4 h interval each, and ultrasonography was performed every 12 h until ovulation. In 11 of 12 cows (92%) the LH surge and ovulation were observed 34.6 ± 1.6 and 59.5 ± 1.9 h, respectively, after removal of progesterone source. The maximum values for LH in those animals were 19.0 ± 2.6 ng/ml (mean ± S.E.M.). It is concluded that, in Nelore cows submitted to a ovarian superstimulation protocol, the LH surge occurs approximately 35 h after removal of intravaginal device containing progesterone, and approximately 12 h before the LH surge observed after an induced estrus without ovarian superstimulation. © 2008 Elsevier B.V. All rights reserved.
Keywords: Bos indicus; Estrous cycle; LH; Superovulation; Zebu cattle; cloprostenol; drug derivative; estradiol; estradiol 3-benzoate; estradiol benzoate; luteinizing hormone; luteolytic agent; progesterone; animal; animal disease; blood; cattle; drug effect; echography; estrus; estrus cycle; female; methodology; ovary follicle; ovulation induction; physiology; superovulation; Animals; Cattle; Cloprostenol; Estradiol; Estrus; Estrus Synchronization; Female; Luteinizing Hormone; Luteolytic Agents; Ovarian Follicle; Ovulation Induction; Progesterone; Animalia; Bos